Pengaruh Brand Image, Kualitas Produk dan Gaya Hidup terhadap Keputusan Pembelian Produk Eiger Kota Surakarta - Dewi Lestari; Asnawi Hidayat; Titin Hargyatni; Pemilia Sulistyowati (Pusat Riset dan Inovasi Nasional, 2026)
every purpose this study is investigate every influence of brand image in every decision to buy Eiger products in Surakarta City, every influence of product quality in every decision to buy Eiger products in Surakarta City, every influence of lifestyle in every decision to buy Eiger products in Surakarta City, also every combined influence of lifestyle, product quality, also brand image. This quantitative investigation's sample size was 70 respondents. A multiple linear regression analysis was conducted with IBM SPSS Statistics. Results of this study show that lifestyle has significant impact every decision to buy Eiger products in Surakarta City, that brand image has positive also significant impact every decision to buy Eiger products in Surakarta City, that product quality has significant impact every decision to buy Eiger products in Surakarta City, also that lifestyle, product quality, also brand image all have an impact every decision to buy Eiger products in Surakarta City at every same time.